2016
DOI: 10.1021/acsami.6b05016
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Paper Electrodes for Li-Ion Batteries Using Low Amount of TEMPO-Oxidized Cellulose Nanofibrils as Binder

Abstract: Flexible Li-ion batteries attract increasing interest for applications in bendable and wearable electronic devices. TEMPO-oxidized cellulose nanofibrils (TOCNF), a renewable material, is a promising candidate as binder for flexible Li-ion batteries with good mechanical properties. Paper batteries can be produced using a water-based paper making process, avoiding the use of toxic solvents. In this work, finely dispersed TOCNF was used and showed good binding properties at concentrations as low as 4 wt %. The TO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 46 publications
(61 reference statements)
1
63
1
Order By: Relevance
“…A bacterial cellulose based separator composed of a cross-linked three dimensional network exhibiting good performance in a battery has likewise been demonstrated (Jiang et al 2015). Since cellulose often contains significant amounts of water it is, however, very important to choose a type of cellulose that contains as little water as possible (Lu et al 2016). We have recently shown that separators made from Cladophora cellulose (CC) are particularly well-suited due to the low water content of this type of cellulose (Pan et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A bacterial cellulose based separator composed of a cross-linked three dimensional network exhibiting good performance in a battery has likewise been demonstrated (Jiang et al 2015). Since cellulose often contains significant amounts of water it is, however, very important to choose a type of cellulose that contains as little water as possible (Lu et al 2016). We have recently shown that separators made from Cladophora cellulose (CC) are particularly well-suited due to the low water content of this type of cellulose (Pan et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Since the rate performance is good (see below), these are sufficient conductivities for usage without additional current collectors. The conductivities can be compared to our previous work, where an LFP/SPC/CNF electrode exhibited a conductivity of around 0.1-1 S m −1 , depending on the component ratios [24]. Even with as much as 11 wt% SPC, the conductivity was no higher than 1.14 S m −1 .…”
Section: Resultsmentioning
confidence: 74%
“…2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO)-oxidized CNF was synthesized following a procedure reported elsewhere [24,29]. The charge density of the CNF was~626 µeq g −1 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations